Hypersurface-homogeneous bulk viscous fluid models with decaying cosmological term - Chandel S.; Singh M.K.; Ram S. (My University, 2025)
We have investigated hypersurface-homogeneous bulk viscous fluid cosmological models with time-dependent cosmological term. It has been shown that the field equations are solvable for any arbitrary scale function.The bulk viscosity coefficient is assumed to be proportional to the energy density. The isotropic pressure and the energy density of the fluid satisfies the barotropic equation of state. The exact solutions of the Einstein's field equations are obtained which represent expanding, shearing and accelerating/decelerating models of the universe. Some physical and kinematical behaviors of the cosmological models are discussed.